(untitled) (Texas Journal of Philology, Culture and History, 2024)
Phatic communication has a psycholinguistic nature, including the addressee, the addressee, and the factors affecting both of them. The speech of the persons entering into communication fully reflects their spirit, consciousness, and psyche. The communicator, of course, has an inner influence on the communicant, and this influence is clearly felt in the language (speech) units of communication